2019
DOI: 10.1002/pmic.201800489
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Tools and Workflow to Select Blood Biomarkers for Early Cancer Diagnosis: An Application to Pancreatic Cancer

Abstract: Secretome proteomics for the discovery of cancer biomarkers holds great potential to improve early cancer diagnosis. A knowledge‐based approach relying on mechanistic criteria related to the type of cancer should help to identify candidates from available “omics” information. With the aim of accelerating the discovery process for novel biomarkers, a set of tools is developed and made available via a Galaxy‐based instance to assist end‐users biologists. These implemented tools proceed by a step‐by‐step strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 37 publications
0
22
0
2
Order By: Relevance
“…However, newer technologies such as proteomics allow large-scale analyses of proteins, including relative abundance and functional inter-relationships, on the same samples. 2428 Although proteomics approaches have been applied to the field of neuroscience, 2930 to date there are no reported studies of sex-dependent differences in mitochondria-related proteins in brain MVs.…”
Section: Introductionmentioning
confidence: 99%
“…However, newer technologies such as proteomics allow large-scale analyses of proteins, including relative abundance and functional inter-relationships, on the same samples. 2428 Although proteomics approaches have been applied to the field of neuroscience, 2930 to date there are no reported studies of sex-dependent differences in mitochondria-related proteins in brain MVs.…”
Section: Introductionmentioning
confidence: 99%
“…Blood circulating biomarkers for detecting early pancreatic cancers have been discovered including circulating tumor DNA [111,112], exome-derived DNA [113], MicroRNA [114] (miR-93, miR-16, miR-548d-3p, etc. ), and proteins [115] (SYCN, REG1B, PRSS2, etc.). Liu et al [112].…”
Section: Application Of Blood Circulating Biomarkers For Detecting Eamentioning
confidence: 99%
“…Traditional methodologies, such as Western blotting, restrict the number of mitochondrial-related proteins in cerebral blood vessels that could be efficiently studied at one time and require a priori 5 decisions concerning protein selection. However, newer technologies such as proteomics allow largescale analyses of proteins, including relative abundance and functional inter-relationships, on the same samples (Brzica et al, 2018;Harman et al, 2018;Javitt & Marbl 2019;Tharakan et al, 2019;Vandenbrouck et al, 2019). Although proteomics approaches have been applied to the field of neuroscience (Gomez-Zepeda et al, 2019;Porte et al, 2017), to date there are no reported studies of sexdependent differences in mitochondria-related proteins in brain MVs.…”
Section: Introductionmentioning
confidence: 99%